The problem of mounting income inequalities in the world vis-a-vis the phenomenon of harmful tax competition. The ICIJ tracking down the greatest financial scandals of the 21st century - Walkowski, Maciej (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2016)
In May 2016, over 350 economists from thirty states signed a letter to global political leaders and the G-7 in particular, warning that tax havens are socially unfair and have no economic justification whatsoever. The author of the best selling Capital in the Twenty-First Century, Thomas Piketty, Professor of Columbia University, the adviser to the UN Secretary General Jeffrey Sachs and Professor of Princeton University and Nobel Winner, Angus Deaton, alongside many renowned academics, called to make the global tax system more transparent and to introduce regulations that would curb the activities of Offshore Financial Centers (OFCs). An NGO Oxfam International, which coordinated the writing of the letter, called upon global leaders to develop a joint standpoint to abandon the secrecy of business operations in tax havens and reveal what harms they bring. According to the analysts from Oxfam, Credit Suisse and UNCTAD, what is called tax optimization actually contributes to greater global income disparities, which are treated as the gravest global issue in the 21st century. The author refers to academic analyses and the results of the journalistic investigations of the International Consortium of Investigative Journalists (ICIJ) in an attempt to diagnose and examine those mutual dependencies and to present the various harms the procedure brings to economies and societies, and presents his own assessment and forecasts for the future.

W maju 2016 roku ponad 350 ekonomistów z 30 krajów świata podpisało się pod listem do światowych liderów politycznych z grupą G-7 na czele, ostrzegając, że działanie rajów podatkowych jest nie tylko niesprawiedliwe społecznie, ale też nie ma współcześnie jakiegokolwiek uzasadnienia ekonomicznego. Autor bestsellerowej pracy naukowej Kapitał w XXI wieku Thomas Piketty, profesor Columbia University i doradca sekretarza generalnego ONZ Jeffrey Sachs, profesor Princeton University i laureat Nagrody Nobla Angus Denton oraz wielu innych cenionych autorytetów naukowych wezwali do wprowadzenia większej przejrzystości w globalnym systemie podatkowym i wprowadzenia regulacji ograniczających funkcjonowanie tzw. OFC. Także organizacja pozarządowa Oxfam International, która koordynowała stworzenie listu, wezwała światowych liderów do ustalenia wspólnego stanowiska w sprawie ukrócenia tajemnicy związanej z funkcjonowaniem spółek w rajach podatkowych, ujawniając szkody, jakie one przynoszą. Tzw. optymalizacja podatkowa w opinii cytowanych w artykule analityków Oxfam, Credit Suisse i UNCTAD przyczynia się do pogłębiania globalnych nierówności dochodowych, traktowanych jako największy problem globalny XXI wieku. Autor, powołując się na ww. analizy naukowe oraz wyniki śledztwa dziennikarskiego Międzynarodowego Zrzeszenia Dziennikarzy Śledczych (ICIJ), stara się zdiagnozować i przybliżyć te wzajemne zależności, ukazać wielorakie szkody, jakie proceder ten przynosi gospodarkom i społeczeństwom, prezentując własne oceny i prognozy na przyszłość.
Problem narastających nierówności dochodowych w świecie a zjawisko szkodliwej konkurencji podatkowej. ICIJ na tropie największych afer finansowych XXI wieku
Keywords: harmful tax competition; global economy; income disparities; tax havens; szkodliwa konkurencja podatkowa; ekonomia globalna; zróżnicowanie dochodowe; raje podatkowe